Mobility biographies: A review of achievements and challenges of the mobility biographies approach and a framework for further research - Müggenburg, Hannah; Busch-Geertsema, Annika; Lanzendorf, Martin (Journal of transport geography, 2015)
•Categorisation of research on life events and their impact on travel behaviour.•Development of a systematic framework for the analysis of travel behaviour change.•Critical discussion of theoretical and methodological challenges and research gaps. In transport research, important changes in an individual’s life, so-called key events, are of particular interest because changes in one’s environment and surrounding context weaken routines, and a ‘window of opportunity’ opens up for behavioural change. In the framework of the mobility biographies approach, several studies have been undertaken to improve understanding of travel behaviour change in the last decade. This paper critically and systematically reviews emerging results from mobility biographies research, focusing on key events which potentially induce contextual and travel behaviour changes. The first step was to identify 25 of the most important studies for this approach and their related concepts. Next, notions other than key events in the literature are discussed and a theoretical framework for the longitudinal interaction of four dimensions of key events and other factors for travel behaviour change are identified: (i) life events in private and professional careers, (ii) adaptation of long-term mobility decisions, (iii) exogenous interventions, and (iv) other long-term processes which are not key events (e.g. socialisation). Furthermore, the understanding of key events, methodological challenges and further research gaps are critically discussed in this review.